Asia and Europe in Japan's Alignment Policies: Drivers, Strategic Expectations and Future Outlook. Issue 3 (27th May 2022) - Atanassova-Cornelis, Elena; Sato, Yoichiro
Abstract : This article examines Japan's security alignments with key Asian and European partners, notably Australia, India, the UK, France and the EU itself. The articles explores Tokyo's strategic expectations with regard to each of the five partnerships, as well as probing the likely future evolution of these alignments by providing a comparative perspective. Japan's alignments with Australia and India conform with and supplement the US-Japan alliance, addressing Japan's primary geostrategic concerns in the Asia-Pacific and the Indian Ocean region. Tokyo's security partnerships with the European partners, and the EU, are more recent and not rooted in any US-led alliance in Asia. The degree of traditional kinetic military power these European players can bring to Asia is very limited. However, the pace with which Japan's new European alignments are quickly moving beyond the non-traditional security areas to encompass more traditional defence and military-security fields attests to their potential of evolving in the future into mechanisms able to perform a broad range of security functions in response to complex security threats. The boundaries between these two categories of partnerships are likely to be further blurred, providing Japan with various mechanisms at different levels to shape and influence the regional and global security environment.